Pengaruh Celebrity Endorser, Daya Tarik Iklan, Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Kecantikan Ms Glow ( Studi Kasus Pada Mahasiswa Feb Unisma Angkatan 2018 ) - Lia Koesmetikawati; Siti Asiyah; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis research was conducted to determine the effect of celebrity endorser, advertising attractiveness and product quality on purchasing decisions of Ms Glow's beauty products. This research uses explanatory research and quantitative approach . by using the Malhotra theory to take a sample, namely the number of items X 5 so that the total sample was found to be 70. To complete this study using validity test, normality test, reliability test, multicollinearity test, heteroscedasticity test, multiple linear analysis, and classical assumption test. This study uses multiple linear analysis with the help of SPSS. The results of this study are celebrity endorser variables, advertising attractiveness, and product quality simultaneously affect consumer purchasing decisions. And partially the celebrity endorser variable has a simultaneous effect on purchasing decisions on Ms Glow products. Keywords: Celebrity endorser, advertising appeal, product quality